Greenhouse heating by energy transfer between greenhouses: System design and implementation. (1st November 2022) - Sun, Weituo; Wei, Xiaoming; Zhou, Baochang; Lu, Chungui; Guo, Wenzhong
Highlights: A greenhouse heating approach utilizing energy transfer between greenhouses is presented. A dual source heat pump with greenhouse and outdoor air sources is designed. An innovative heating load model and a surplus air heat model are developed. The greenhouse heating system was built and followed with a pilot study. COP of heat pumps was improved by 23–26% due to usage of greenhouse air source. Abstract: Multi-span greenhouses consume enormous amounts of energy for heating in northern China, resulting in poor profitability and unsustainability. A greenhouse heating system, utilizing energy transfer between greenhouses based on a dual source heat pump, was designed to remedy this issue. The system collects surplus air heat inside Chinese solar greenhouses (CSGs) for heating multi-span greenhouses. Through enabling a greenhouse energy transfer in time and space, improved utilization efficiency of surplus air heat in CSGs is achievable, resulting in an overall reduction of heating costs. This study defines the heating approach and describes the overall system design. The dual source heat pump acts as the core component, with two separate evaporators placed in the CSG and ambient air. Calculations for system sizing are then presented, including a heating load model of multi-span greenhouses, a surplus air heat model of CSGs, the selection of required equipment (dual source heat pump, heat storage tank, and surface air cooler of the combined air conditioning unit), and the area matching. Finally, a case study illustrates the implementation processes of the heating system. The available CSG surplus air heat ranged 100.8–112.6 W m −2 for system sizing, and the minimum area of CSGs was suggested to be twice the multi-span greenhouse area. The pilot test showed that the running status and heating effect of the system was stable. The coefficient of performance (COP) of the heat pump reached 4.3–4.8 when using CSG surplus air heat as the heat source, performing 23–26 % higher than when using ambient air over the same periods. Throughout the entire course of heat collection, dual source heat pumps, switching sources based on their setting, achieved a total COP of 3.4–4.2, increased by 6–11 % compared with air source heat pumps. This study provides a novel heating approach and an energy-saving system for multi-span greenhouses.